2021
DOI: 10.1111/scd.12603
|View full text |Cite
|
Sign up to set email alerts
|

A bio‐behavioral intervention combining task analysis with skill‐based training to train toothbrushing among children with intellectual disability

Abstract: Individuals with intellectual disability (ID) have special health care needs.Teaching self-care behaviors like toothbrushing helps reduce their dependence on adult caregivers. We present a bio-behavioral intervention combining task analysis with skill-based teaching of toothbrushing behavior aimed to promote autonomy in children with various types of ID. Methods: One hundred twenty children with ID enrolled at a special school in the State were included in the study. After baseline measurements using task anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…21,27 Gaunkar et al found that task analysis with skill-based teaching of toothbrushing promoted autonomous performance in special needs child after 4 weeks and suggested that this method is practical and could reduce their dependence on caregivers. 25 The present study confirmed that school teachers can provide oral hygiene education; the results were satisfactory and consistent with those of Joybell and Krishnan. 11 Therefore, we suggest that for visually impaired persons, a specially designed multisensory program or guideline of oral health education should be established in the school curriculum.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…21,27 Gaunkar et al found that task analysis with skill-based teaching of toothbrushing promoted autonomous performance in special needs child after 4 weeks and suggested that this method is practical and could reduce their dependence on caregivers. 25 The present study confirmed that school teachers can provide oral hygiene education; the results were satisfactory and consistent with those of Joybell and Krishnan. 11 Therefore, we suggest that for visually impaired persons, a specially designed multisensory program or guideline of oral health education should be established in the school curriculum.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, most participants in the study were not totally blind and had intact intellectual abilities; thus, there was a high degree of communication with the teacher and their muscle coordination was satisfactory. Therefore, there were no intellectual disabilities that could affect the motor skills required for brushing skill acquisition 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data, on the level of prompting needed to complete each step, are collected to monitor progress and make instructional decisions such as when to add the next step in the chain, or break a current step into even more discrete behaviors. The use of task analysis for instruction has a solid evidence base and has been used widely to teach a variety of skills to individuals with ID such as daily living skills (Bridges, Robinson, Stewart, Kwon, & Mutua, 2020), self-care-skills (Gaunkar et al, 2021), and academic content (Browder et al, 2018). Some of the digital literacy skills taught using task analysis include accessing, replying, composing, and sending emails on multiple devices (Cihak, McMahon, Smith, Wright, & Gibbons, 2015a) as well as bookmarking, downloading, and uploading documents (Cihak et al, 2015b).…”
Section: The Internet and Multiple Devicesmentioning
confidence: 99%